Human-edible protein contribution of tropical beef cattle production systems at different levels of intensification - Fernandes, M. H. M. R. [UNESP]; Cardoso, A. S. [UNESP]; Lima, L. O. [UNESP]; Berça, A. S. [UNESP]; Reis, R. A. [UNESP] (Elsevier, 2022)
Sustainable intensification of tropical grasslands has been identified by researchers and stakeholders as a solution to decrease greenhouse gas emissions and deforestation. However, there are concerns about food security and the role of livestock in feed-food competition between animals and humans involving land and other resources. We aimed to determine the net protein contribution (NPC), a feed-food competitiveness index, of tropical beef cattle raised on extensive systems or finished in pastures or conventional feedlots, under different levels of intensification. We modelled five scenarios, from cow-calf to slaughter, based on common beef cattle practices in Brazil, whose main production system is grazing. Scenario 1 represented the lowest level of intensification and the most extensive system. Scenario 2 represented a moderately extensive system. Scenarios 3, 4, and 5 represented different degrees and practices of intensification, with animals in cow-calf and stocker phases raised solely on well-managed permanent pastures. In Scenario 3, the animals were finished in a feedlot. In Scenarios 4 and 5, all animals in the stocker phase received a protein-energy supplement, but in Scenario 4, animals were finished in a permanent pasture with high-concentrate intake. In Scenario 5, animals were finished in a feedlot. The human-edible protein (heP) conversion efficiency (hePCE) was calculated as the ratio of heP produced (meat) to heP consumed as feed, and the NPC was the product of hePCE using the protein quality ratio, accounting for the digestible indispensable amino acid score content. An hePCE > 1 indicated that meat production did not compete with humans for food, and an NPC > 1 indicated that it contributed positively to meet human requirements. Meat production and heP intake consistently increased with intensification. The greatest hePCE values were from Scenarios 1 (9.2), 2 (2.2), and 3 (1.2), which were essentially pasture-fed systems, compared to Scenarios 4 and 5 (average of 1.0). The NPC varied from 24.1 (Scenario 1) to 2.6 (Scenario 5). The area required to produce 1 kg of carcass decreased from 147 to 45 m2, and the slaughter age decreased from 36 to 21 months from the most extensive to intensive systems. Brazilian beef cattle production contributes positively to the protein requirements of humans without limiting human food supplies. The intensification of tropical grazing beef systems is a key strategy to save land and produce more meat without limiting food for humans, playing an important role in the food security agenda.
Keywords: Food security; Meat; Nellore; Sustainability; Tropical grassland